Anti-Hu Antibody Associated Paraneoplastic Cerebellar Degeneration in Head and Neck Cancer. Issue 1 (December 2015) - Huemer, Florian; Melchardt, Thomas; Tränkenschuh, Wolfgang; Neureiter, Daniel; Moser, Gerhard; Magnes, Teresa; Weiss, Lukas; Schlattau, Alexander; Hufnagl, Clemens; Ricken, Gerda; Höftberger, Romana; Greil, Richard; et al.
Abstract Background Paraneoplastic syndromes are most frequently associated with small cell lung carcinoma, hematologic and gynecologic malignancies while reports in head and neck cancer are rare. Case presentation We present the case of a 60-year old female patient who developed paraneoplastic cerebellar degeneration upon locoregional recurrence of a poorly differentiated spindle cell carcinoma of the nasal cavity and paranasal sinus. The neurological symptoms, especially ataxia, stabilized after resection of tumor recurrence and concomitant chemoradiotherapy whereas anti-Hu-antibodies remained positive. Despite the unfavorable prognosis of paraneoplastic neurological disorders associated with onconeural antibodies, the patient achieved long-standing stabilization of neurological symptoms. Conclusion We report the first patient with anti-Hu antibodies and paraneoplastic cerebellar degeneration associated with a spindle cell carcinoma of the head and neck. We recommend that evaluation of neurological symptoms in patients with this tumor entity should also include paraneoplastic syndromes as differential diagnoses and suggest early extensive screening for onconeural antibodies.